Evaluation of chromatographic dead times for retention indices determination in RP-HPLC using some homologous series - Rinaldi Idroes (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Dead time that defined as a retention time of unretained substance in the chromatographic coloumn, is needed to determine all retention parameters in coloumn chromatography such as corrected retention time, relative retention time and Kovats Retention Indices.This research reported a comparison between the iteration and linearization of corrected retention times of homologous series such as n-alkane, akylrylketone, alkylbenzene and 2-alkanone. Furthermore the iteration method provides better dead-time values and smaller standard deviations than the linearization method. Moreover, the dead-time calculation obtained according to homologous series is not depending on solvent composition for various homologous series.The n-alkane homologous series show better indication accuracy of fit (S/N) in comparison with other homologous series, thereafter 2-alkanone exhibit the second best adjustment.Keywords: Dead-time evaluation, homologous series, methanol/water solvent, RP-HPLC.